ответ:Cos (x – π/3) = √2/2;
1) (x – π/3) = π/4 + 2 * π * n; n ϵ Z;
2) (x – π/3) = -π/4 + 2 * π * n; n ϵ Z;
Теперь найдем сами корни уравнения:
x = π/4 + п/3 + 2 * π * n;
x = (7 * п)/12 + 2 * п * n, n ϵ Z;
2) (x – π/3) = -π/4 + 2 * π * n;
x = -π/4 + π/3 + 2 * π * n;
x = п/12 + 2 * п * n, n ϵ Z;
Пошаговое объяснение:
ответ:Cos (x – π/3) = √2/2;
1) (x – π/3) = π/4 + 2 * π * n; n ϵ Z;
2) (x – π/3) = -π/4 + 2 * π * n; n ϵ Z;
Теперь найдем сами корни уравнения:
1) (x – π/3) = π/4 + 2 * π * n; n ϵ Z;
x = π/4 + п/3 + 2 * π * n;
x = (7 * п)/12 + 2 * п * n, n ϵ Z;
2) (x – π/3) = -π/4 + 2 * π * n;
x = -π/4 + π/3 + 2 * π * n;
x = п/12 + 2 * п * n, n ϵ Z;
Пошаговое объяснение: